The Islamic Marketing and Branding in Europe - Ameur, Ahmed Ameur (International Journal of Islamic Banking and Finance Research, 2018)
The Islamic markets, labelled “Halal Markets”, are nowadays experiencing an active, an amplified and a wide spread which drawa lot of attention in Europe; this led many researchers and academics to delve in this area, besides setting a base to “Islamic Marketing” which goes with the western actuality along with competing in the capitalist traditional market.In the following paper, we exposetwo conflicting elements, in an attempt to examine and analyse them; on the one hand, we attempt to address Western companies’ radicalism, in its pureWestern production orientation; on the other hand, the Islamic lifestyle among youth, overseas Muslims’ children.By the end of the paper, we concluded that numerous Western companies succeeded locally,via exploiting the Islam Pillars, in conquering the Islamic market by which they founded the Islamic marketing in Europe, obtained huge profits. In addition to that, it succeeded in tamingoverseas young generation, who were looking for a typical halal lifestyle and creating their own lifestyle based on a culture built on well-established Islamic beliefs.